Ответы и объяснения

2014-02-02T15:25:05+00:00
С-26
Вариант 1
№1
а) 12а-4а^2+10-2а+а^2= -3а^2+10а+10
б) 2r*1/2r^2-3r*2/3r+2r*4r-5r*3/5+7-4r=r^3+6r^2-7r+7
№2
p(m)=5m^3-3-2m-8m^3-m= -3m^3-3m-3= -3(m^3+m+1)
p(-2)= -3(-8-2+1)= -3*(-9)=27

Вариант 2
№1
а) 7x^3+5x^2-4x-3x^2-7x^3+9= 2x^2-4x+9
б) 3p*5/6p+15p*4/5p^2-9/2p^2+2p*3/4-3+2p^3= 5/2p^2+12p^3-9/2p^2+3/2p-3+2p^3= 14p^3-2p^2+1,5p-3
№2
p(a)= a^2-4a-9a^2-a-2= 10a^2-5a-2= 2(5a^2-2,5a-1)
p(-3)= 2(45+7,5-1)= 2*51,5=103

Вариант 3
№1 
а) 9c^4+2c-5c^2+7-2c-c^2= 9c^4-6c^2+7
б) 5y^2*1/2y+1/4y*8y+3y-2y*1/6y-0,5y*y^2+1= 2,5y^3+2y^2+3y-1/3y^2-0,5y^3+1= 2y^3+2/3y^2+3y+1
№2
p(x,y)= x^3-3x^2y+xy^2-y^3+6x^2y+xy^2-x^3= 3x^2y+2xy^2-y^3= y(3x^2+2xy-y^2)
p(-2;-1)= -1(12+4+1)= -17

Вариант 4
№1
а) 10b^2+b^3-4b^2+1-3b+5= 6b^2+b^3-3b+5= b^3+6b^2-3b+5
б) 3/2t*7/3t^2-8t*3/4t+4/7t-t*2t-t^2*3,5t-2= 3,5t^3-6t^2+4/7t-2t^2-3,5t^3-2= -8t^2+4/7t-2
№2
p(x,y)= x^4+4x^2y-6x^2y^2+4xy^3-x^4+y^4+6x^2y^2+y^4= 4x^2y+4xy^3+2y^4= 2y(2x^2+2xy^2+y^3)
p(-3;-1)= 2(18-6+1)= 26


С-27
Вариант 1
№1
p1(x)+p2(x)= 5x^2-4x+1+6x^2+x-3= 11x^2-3x-2
p1(x)-p2(x)= 5x^2-4x+1-6x^2-x+3= -x^2-5x+4
№2
x^2+(5x-2)-(3x+1)=3x+x^2
5x-3x-3x=3
-x=3
x= -3

Вариант 3
№1
p1(x)+p2(x)= 2x^3-3x+1-x^3-2x-1= x^3-5x
p1(x)-p2(x)= 2x^3-3x+1+x^3+2x+1= 3x^3-x+2
№2
2y^2-(5+6y)+(y-2y^2)=9-7y
2y^2-5-6y+y-2y^2=9-7y
-6y+y+7y=9+5
2y=14
y=7